Book Review: Floods in a Changing Climate. Inundation Modelling - Esa Hidayat (Fakultas Seni Rupa dan Desain ITB, 2022)
This book is organized into eleven chapters and consists of three parts with different characteristics to discuss. Written by Giulano Di Baldassare as lead author and in certain chapters contributed by other authors: Paul D. Bates, Timothy J. Fewtrell, and Jeffrey C. Neal in Chapter 8; Luigia Brandimarte in Chapter 2; and Ioana Popescu in Chapter 3. Giulano Di Baldassare is known as a researcher and senior lecturer at the UNESCO-IHE for Water Education based in Delft, The Netherlands. His lectures included: hydrodynamics and remote sensing, hydrological statistics, flood management, and others related to fluids and hydraulic field. As an academic, Dr. Di Baldassare has authored more than 30 peer-reviewed journals, 60 other scientific articles, and was awarded the Outstanding Young Scientist Award from the European Geosciences Union. In addition, he applied practical his knowledge to projects relate to flood disaster mitigation, such as the coordinator of the FP7 KULTURisk EC project.